Improving MSME HR Competence through Performance Management Training and Effective Recruitment - Dahlena, Alni; Soni, Mohammad; Lindayani, Lindayani; Hamdani, Nizar Alam; Safari, Shabina Meisya Andriani; Annisa, Nayila Sifa Nurul (Indonesian Journal of Community Empowerment (IJCE), 2025)
Effective performance management and recruitment training are urgently needed for MSMEs. Effective human resource management is crucial for building a strong work team and supporting business sustainability. The integration of performance management and recruitment training is rarely examined as a single program. The training is implemented through interactive lectures, case studies, discussions, simulations, and evaluations. This training employs a participatory and applied approach, prioritizing the active involvement of MSME participants throughout the entire process. The results of the performance management training demonstrate that MSMEs need to develop the skills to develop key performance indicators (KPIs), regularly monitor and evaluate employee performance, and provide constructive feedback. The recruitment process is also a weak point for many MSMEs. Therefore, a sustainable strategy for strengthening MSME human resource capacity, oriented toward increasing productivity, operational efficiency, and business competitiveness amidst increasingly competitive economic challenges, is essential.